Role of Digital Transformation and Innovation in Enhancing the Competitiveness and Sustainability of Hospitality and Tourism Businesses in South Africa - Abeba , Lubanzi (International Journal of Modern Hospitality and Tourism, 2024)
Purpose: The study sought to analyze the role of digital transformation and innovation in enhancing the competitiveness and sustainability of hospitality and tourism businesses Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: Digital transformation and innovation are essential drivers for enhancing the competitiveness and sustainability of hospitality and tourism businesses in South Africa. By embracing digital technologies, businesses can improve customer experiences, increase operational efficiency, make data-driven decisions, and adapt to changing market dynamics, ultimately securing their position in the evolving industry landscape. Unique Contribution to Theory, Practice and Policy: Resource-Based View (RBV), Dynamic capabilities theory & Disruptive innovation theory may be used to anchor future studies in the role of digital transformation and innovation in enhancing the competitiveness and sustainability of hospitality and tourism businesses. Encourage research that explores the intersection of digital transformation, innovation, and competitiveness within the hospitality and tourism sector. Promote the adoption of digital technologies and innovation strategies among hospitality and tourism businesses.